The Use of the Problem-Based Learning (PBL) Model to Improve Islamic Education Learning Outcomes for Elementary School Students - Mike Hafidah; Ahmad Syarifin (Jurnal Indonesia Pendidikan Profesi Guru, 2024)
Objective: The purpose of this study was to determine the effect of applying the Problem-Based Learning (PBL) model in improving learning outcomes in Islamic Religious Education, specifically on the asmaul husna material, at SDN 58 Bengkulu Selatan. Method: This research is classroom action research (CAR) conducted in 2023 at SDN 58 Bengkulu Selatan. The subjects of the study were 20 fourth-grade students. Data were collected using test and non-test techniques, including observation sheets and student learning outcomes. Data analysis involved reviewing both observation results and test scores across research cycles. Result: The study showed that the application of the Problem-Based Learning model improved students' Islamic Religious Education learning outcomes. This improvement was evidenced by the increasing test scores achieved by students in each cycle of the intervention. Conclusion:The implementation of Problem-Based Learning can effectively enhance students' understanding and performance in Islamic Religious Education, especially in learning the asmaul husna material. Contribution: This study contributes practical insights for educators, highlighting that integrating PBL into religious education can actively engage students and lead to better learning outcomes, particularly in primary school contexts.